2019
DOI: 10.5860/crl.80.6.843
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Standardization and Consistency Issues in Repository Metadata Requirements for Data Deposition

Abstract: We examine common and unique metadata requirements and their levels of description, determined by the data deposit forms of 20 repositories in three disciplinesarchaeology, quantitative social science, and zoology. The results reveal that requirements relating to Creator, Description, Contributor, Date, Relation, and Location are common, whereas those regarding Publisher and Language are rarely listed across the disciplines. Data-level descriptions are more common than study-and file-level descriptions. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In order to understand and judge data quality, data reusers need basic or intrinsic metadata (e.g., the identity of data creator, date of creation, and terms of use), information on the context and methods of data creation (Kim, Yakel, and Faniel 2019), and processual information (i.e., paradata)-for example, declaration of selection and exclusion decisions made during the research process (Allison 2008)-about the data creation. Koesten et al (2020) identify common features associated with the reuse potential of datasets in an extensive review of data reuse literature across several disciplines.…”
Section: Needs and Challenges In Data Reusementioning
confidence: 99%
“…In order to understand and judge data quality, data reusers need basic or intrinsic metadata (e.g., the identity of data creator, date of creation, and terms of use), information on the context and methods of data creation (Kim, Yakel, and Faniel 2019), and processual information (i.e., paradata)-for example, declaration of selection and exclusion decisions made during the research process (Allison 2008)-about the data creation. Koesten et al (2020) identify common features associated with the reuse potential of datasets in an extensive review of data reuse literature across several disciplines.…”
Section: Needs and Challenges In Data Reusementioning
confidence: 99%
“…Finding no universally applied standard and noting that "56 unique fields were identified from the 15 example data items," the study concludes by reminding the reader that through "robust metadata, curated research data repositories will be discoverable, usable, and interoperable into the future independent of the repository platform" (p. 10). The study by Kim et al (2019) of metadata practices across 20 repositories in three academic disciplines provided the initial impetus for our present study of academic IRs. We borrow heavily from their framework and methodology, particularly, the idea that documentation-data deposit forms and attendant guidelines-"performs the dual purposes of defining a contract between depositors and repositories and gathering information about the deposited data" (p. 843).…”
Section: )mentioning
confidence: 99%
“…After using MS Excel to assign a random number to each row of the master CSV, we sorted the universe in ascending numerical order. Using the methodology from Kim et al (2019) as broad inspiration as well as some targeted elements specific to our inquiry, we developed a coding scheme. Beginning with two IRs randomly selected from the universe, we performed time trial and simplified interrater agreement testing to determine variance in code assignments.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of standardization and the problem of granularity in describing data have been discussed in other studies regarding data documentation and metadata [10][11][12]. Those studies also indicated that documenting an adequate amount of proper contextual information about data would increase the potential for data reuse.…”
Section: Introductionmentioning
confidence: 99%